ColorSafe: Architectural Support for Debugging and Dynamically Avoiding Multi-Variable Atomicity Violations - Lucia, Brandon; Ceze, Luis; Strauss, Karin (ISCA 2010 (International Symposium on Computer Architecture), 2010)
In this paper, we propose ColorSafe, an architecture that detects and dynamically avoids single- and multi-variable atomicity violation bugs. The key idea is to group related data into colors and then monitor access interleavings in the “color space”. This enables detection of atomicity violations involving any data of the same color. We leverage support for meta-data to maintain color information, and signatures to efficiently keep recent color access histories. ColorSafe dynamically avoids atomicity violations by inserting ephemeral transactions that prevent erroneous interleavings. ColorSafe has two modes of operation: (1) debugging mode makes detection more precise, producing fewer false positives and collecting more information; and, (2) deployment mode provides robust, efficient dynamic bug avoidance with less precise detection. This makes ColorSafe useful throughout the lifetime of programs, not just during development. Our results show that, in deployment mode, ColorSafe is able to successfully avoid the majority of multivariable atomicity violations in bug kernels, as well as in large applications (Apache and MySQL). In debugging mode, ColorSafe detects bugs with few false positives.